Letter (copy) : Spanish seamen: cards - Tewson, Vincent
025a-0089-001 International HVT/AC/301 13th July, 1939. Señor A. de Gondra, Basque Delegation, 14, Eccleston Sq., S.W. 1. Dear Mr. de Gondra, SPANISH SEAMEN: CARDS. We have been discussing with the British Committee for Refugees from Spain the transport question for the Spanish seamen whom we are hoping to emigrate soon. The Committee informs us that one of its difficulties is that there is a lack of uniformity in the various ports in the method of completing the cards. The problem facing the Committee is to find out whether the Mexican Minister will allow passports, and, until it knows the names of the men, it cannot send them to the Mexican Minister and thus take the next step in the work of emigration. The Committee wants a comprehensive report, covering each port where the men are located, and stating whether the men have filled in the cards and where the cards have been sent. Then, an up-to-date list of the men must be secured, with the desired destinations, and grouped into the various ports. It is pointed out to us that there might be transport from France - not perhaps in the immediate future; but a possibility of transport might arise at any time, and the Committee must have this Information before they can take advantage of it. I have written this letter since I have not been successful in reaching you on the telephone, and I am sure you will wish to look into the points the Committee has raised. Yours sincerely, Assitant Secretary 292/946/25a/89